The Factors That Cause Low Interest in Learning in Grade 4 Students at SDN 3 Perian - Khotmi, Nurmaulia; Hidayati, Riska; Hidayati, Yuliana (Jurnal Ilmiah Mandala Education (JIME), 2024)
Low interest in learning in students is generally caused by two factors, namely internal factors and external factors. Internal factors arise from within the students themselves, such as health, mental readiness, intelligence level, interest and so on. External factors are factors that come from outside the student, such as the environment, family, community, friends, teachers, media, learning facilities and infrastructure.The purpose of this research is to find out what factors can cause low interest in learning in students. The method used in this research is a qualitative approach with the type of approach is descriptive research, the research subjects are homeroom teachers and student guardians with data collection techniques interviews, observations and documents through student learning outcomes report cards. The results of this study reveal that low student interest in learning is due to students' lack of interest or interest in learning in the classroom. The lack of interest in learning in students is due to the learning methods used by teachers are still old methods, lack of innovation from teachers such as not developing teaching materials with teaching aids when teaching. Inadequate facilities and infrastructure can also be a factor in causing low interest in learning such as buildings for learning classes that are lacking, benches and tables that are no longer suitable for use and lack of other learning support tools. In addition, the lack of support from the environment, both parents and teachers, can also cause low interest in learning.